Permasalahan Kualitas Tenaga Pendidik PAUD dan Implikasinya terhadap Perkembangan Anak - Nia Ramadani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze in depth the quality of Early Childhood Education (ECE) teachers in the learning process at schools and its implications for early childhood development. The quality of educators is viewed as one of the key factors determining the success of learning implementation and the achievement of educational objectives at the early childhood education level. This study employs a literature review method, which involves collecting various relevant scientific articles, books, and other academic sources related to the research topic, followed by systematic analysis to obtain a comprehensive understanding and conclude the findings. The results indicate that the quality of educators has a significant influence on teachers’ success in performing their roles as facilitators, mentors, and educators in supporting children’s cognitive, social, emotional, and motor development. Therefore, the quality of early childhood educators needs to be continuously developed and improved through education, training, and professional development to maintain and enhance the quality of learning activities in schools. In addition, support from various stakeholders, including the government, educational institutions, schools, and parents, plays a crucial role in efforts to improve the quality of early childhood educators in an optimal and sustainable manner.